2019
DOI: 10.3389/fcimb.2019.00104
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis and Virulence Assessment of Granulicatella adiacens Secretome

Abstract: Despite reports on the occurrence of Granulicatella adiacens in infective endocarditis, few mechanistic studies on its virulence characteristics or pathogenicity are available. Proteins secreted by this species may act as determinants of host-microbe interaction and play a role in virulence. Our aim in this study was to investigate and functionally characterize the secretome of G. adiacens . Proteins in the secretome preparation were digested by trypsin and applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 93 publications
0
11
0
Order By: Relevance
“…In addition, we noticed that among the 12 secreted proteases, only 5 have a predicted signal peptide, that is, 1 M4 protease, 1 S8 protease, 1 S11 protease, 1 C40 protease, and 1 M23 protease, which are likely secreted by signal peptide-mediated translocation. The other 7 secreted proteases without a predicted signal peptide might be secreted outside the cell via other secretion systems, such as the twin-arginine transport pathway, or a non-classical secretory system ( Karched et al, 2019 ). As shown in Table 3 , there are 10 putative proteases with a predicted signal peptide in strain 1A02591.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we noticed that among the 12 secreted proteases, only 5 have a predicted signal peptide, that is, 1 M4 protease, 1 S8 protease, 1 S11 protease, 1 C40 protease, and 1 M23 protease, which are likely secreted by signal peptide-mediated translocation. The other 7 secreted proteases without a predicted signal peptide might be secreted outside the cell via other secretion systems, such as the twin-arginine transport pathway, or a non-classical secretory system ( Karched et al, 2019 ). As shown in Table 3 , there are 10 putative proteases with a predicted signal peptide in strain 1A02591.…”
Section: Resultsmentioning
confidence: 99%
“… 2 G. adiacens is a type of nutritionally variant streptococcus found as part of the normal microbiota in the oral cavity and is an uncommon source of infection. 3 They are found in dental plaque and can cause endodontic infection and dental abscesses. However, they can also cause more serious bloodstream infections including endocarditis or device infections.…”
Section: Discussionmentioning
confidence: 99%
“…Initial bioinformatic analyses indicated that the majority of the modified proteins were predicted to be cytoplasmic, with only 3% predicted to be secreted (Supplementary Tables 7, 8). However, it is well known that many predicted cytoplasmic proteins can also be secreted, e.g., DnaK (Karched et al, 2019), EF-Tu (Chiu et al, 2017), and GroEL (Jeffery C.J., 2018). Such multifunctional proteins are also known as moonlighting proteins and may be involved in adhesion to the host or in microbial pathogenesis (Hagemann et al, 2017;Harvey et al, 2019;Jeffery C.J., 2019;N'Diaye et al, 2019).…”
Section: Phospho-secretome Analysis Of a Baumannii Strains Atcc 17978 And Ab0057mentioning
confidence: 99%